2011
DOI: 10.1037/a0020699
|View full text |Cite
|
Sign up to set email alerts
|

Democracy under uncertainty: The wisdom of crowds and the free-rider problem in group decision making.

Abstract: We introduce a game theory model of individual decisions to cooperate by contributing personal resources to group decisions versus by free-riding on the contributions of other members. In contrast to most public-goods games that assume group returns are linear in individual contributions, the present model assumes decreasing marginal group production as a function of aggregate individual contributions. This diminishing marginal returns assumption is more realistic and generates starkly different predictions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 101 publications
3
56
1
Order By: Relevance
“…When participants believed that their own choices were consistent with the majority's choice, 21% of them changed their choices to the less popular project, but all of the participants in the Minority condition retained their minority choice. Considering the robust phenomenon of majority-influence in social decision making (Hastie & Kameda, 2005;Kameda, Tsukasaki, Hastie, & Berg, 2011), the anti-conformity pattern here is the opposite of the typical social influence observed in many attitudinal judgments (Cialdini & Goldstein, 2004;Salganik et al, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…When participants believed that their own choices were consistent with the majority's choice, 21% of them changed their choices to the less popular project, but all of the participants in the Minority condition retained their minority choice. Considering the robust phenomenon of majority-influence in social decision making (Hastie & Kameda, 2005;Kameda, Tsukasaki, Hastie, & Berg, 2011), the anti-conformity pattern here is the opposite of the typical social influence observed in many attitudinal judgments (Cialdini & Goldstein, 2004;Salganik et al, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…Results from both computer simulations and laboratory experiments showed that the majority rule fared quite well, performing at levels comparable to much more computationally taxing rules. Furthermore, the majority rule outperformed the despotic best member rule, even when members were not forced to cooperate for group endeavor and free riding was possible (Kameda et al, 2011).…”
Section: Despotism Versus Democracymentioning
confidence: 99%
“…However, coordination might not be so desirable in this occasion. The problem with players conforming with the majoritarian direction or mimicking each other is that they will be subject to herding effects [50] [51] which in this particular setting can be catastrophic due to the lag present in the system. Indeed, if we set the probabilities in our model so that the next state in the transition is always the one that gets you closer to the exit but with 25 seconds of delay (that is, the probability of going from state x m to x m+1 is the probability of going from x m−n to the state which follows the optimal path), the system gets stuck in a loop and is never able to reach the exit.…”
Section: A the Ledgementioning
confidence: 99%